RELATIONSHIP BETWEEN CLINICAL EVALUATION OF ACUTE FETAL DISTRESS, MODE OF DELIVERY AND CONDITION OF THE NEWBORN - Gonzáles, Miren (2015)
A study was conducted in 1352 live births, 1344 deliveries have taken place in the "Edgardo Rebagliati Martins" National Hospital - IPSS - in Lima, between 1 and May 31, 1985, in order to determine the incidence of suffering acute fetal (SFA) compensated or decompensated. It detected 215 (15.90%) of SFA, 172 (12.72%) of whom belonged to group A and 43 (3.18%) in group B, having found a higher incidence of fetal distress to that reported in the literature unbalanced. Pregnancy hypertensive disease was most often related to breast pathology SFA. Cesarean section was performed in 27% of the population in distress. Caesarean section and instrumental delivery had a high incidence in the group with decompensated (55.81% and 27.91%, respectively) SFA, recording no statistically significant differences between groups and offset control. The Apgar in newborns with SFA was lower than in the control group significantly. Morbidity was higher in infants with SFA than in the control group, with statistically significant differences: In group A, 26.16% presented some pathology, and B, the 34.88%, more frequent hypoxia and difficulty syndrome Respiratory. Obstetric trauma was the most frequent pathology in group B. The neonatal mortality, assessed in the study period was 0.93% and was 3.73% perinatal. The causes of death were neonatal necrotizing enterocolitis and hemorrhagic disease of the newborn.